INTEGRATING ARTIFICIAL INTELLIGENCE IN ISLAMIC EDUCATION: ETHICAL, PEDAGOGICAL, AND SUSTAINABILITY PERSPECTIVES - Khoiruddin, M. Arif; Dzulkifli, Izuli (Prodi Pendidikan Agama Islam STAI Darul Falah, 2026)
Integrating Artificial Intelligence (AI) into Islamic education represents a significant advancement in educational innovation, offering new possibilities for enhancing learning experiences, expanding access, and supporting curriculum development. However, its implementation must be approached with caution to ensure alignment with Islamic ethical principles, educational traditions, and cultural diversity. This qualitative, literature-based study systematically analyzes peer-reviewed articles, reports, and books published between 2019 and 2024 to explore the potentials and challenges of AI in Islamic education. The study focuses on three critical aspects: (1) the development of AI technologies that comply with Islamic values and shariah, (2) teacher training for value-conscious and effective AI use, and (3) sustainability strategies for long-term integration. Findings suggest that while AI offers promising solutions for personalization and accessibility, its effectiveness depends on ethical oversight, technological infrastructure, and pedagogical readiness. This study proposes a conceptual framework to guide responsible AI integration in Islamic education, contributing to developing future-ready and values-driven educational models.